The Sabethines of Northern Andean Coffee-Growing Regions of Colombia (2015)
ABSTRACT: Sampling for sabethine mosquitoes occurred intermittently from September 2007 to April 2013 in 17 municipalities, located in 5 departments (divisions) in the northern Andean coffee-growing regions of Colombia. Of the 9 genera within the Sabethini tribe known to occur in the Neotropical region, 6 were encountered including 15 species: Jonhbelkinia ulopus, Limatus durhamii, Sabethes ignotus, Sa. luxodens, Sa. undosus, Shannoniana fluviatilis, Trichoprosopon compressum, Tr. digitatum, Tr. evansae, Tr. pallidiventer s.l., Tr. pallidiventer s.s., Wyeomyia arthrostigma, Wy. oblita, Wy. ulocoma, and Wy. undulata. The species Sa. luxodens and Wy. undulata constitute new records for Colombia. These records broaden the knowledge of this important group that includes some important species related to the arbovirus transmission. Records are from the northern Colombian Andes, a region noted for coffee cultivation and ecotourism.